Are we done fighting?: building understanding in a world of hate and division - Legge, Matthew (New Society Publishers, 2019)
"Are We Done Fighting? provides research, practical activities, and inspirational stories of success for cultivating inner change and spreading peace at the community level and beyond. Essential for everyone working to build understanding as an antidote to the politics of hate and division."--